A thermoelectric composite material and its preparation method and application
Through the composite of Ag2Se and Ti3C2Tx, a high-performance n-type Ag2Se/Ti3C2Tx thermoelectric composite material was prepared, which solved the problem that it is difficult to obtain flexible Ag2Se thermoelectric films with high flexibility and high thermoelectric properties in the prior art, and achieved the effect of high power factor and low thermal conductivity.
Patent Information
- Application Number
- CN202411655047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to reduce the use of insulators while maintaining the Ag2Se nanostructure and obtain a flexible Ag2Se thermoelectric film with high flexibility and high thermoelectric properties.
By compounding Ag2Se with Ti3C2Tx, an Ag2Se/Ti3C2Tx composite structure is prepared, interface, multi-stage energy bands and defects are introduced, phonon scattering is enhanced, and high power factor and low thermal conductivity are achieved.
It realizes a high-performance n-type Ag2Se/Ti3C2Tx thermoelectric composite material, with excellent thermoelectric properties and flexibility, and is suitable for the preparation of flexible thermoelectric films.
Smart Images

Figure HDA0005141924240000011 
Figure HDA0005141924240000012 
Figure HDA0005141924240000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible thermoelectric film preparation and relates to an n-type Ag 2 Se / Ti 3 C 2 T x Thermoelectric composite material, preparation method thereof and application in preparing flexible film. Background Art
[0002] Flexible thermoelectric generators are an ideal energy supply method for wearable electronic devices because they are easy to wear and integrate, can directly generate electricity using the temperature difference between human body temperature and the external environment, have no mechanical vibration, are maintenance-free, and provide sustainable power supply. For flexible thermoelectric devices, the thermoelectric materials that make up the device are the key to determining its performance.
[0003] Flexible thermoelectric materials are usually composed of three types of material systems: the first type is conductive polymers, which are also the most studied flexible thermoelectric materials at present, mainly including polyethylene benzene sulfonic acid doped poly (3, 4-ethylenedioxythiophene) (PEDOT: PSS) and polyaniline (PANI). By adjusting the doping degree of conductive polymers, their conductivity can be effectively optimized, but the Seebeck coefficient / resistance measurement is low. The second type is carbon nanotubes (CNTs) and graphene with high conductivity and carrier mobility. The thermal conductivity of the CNTs network formed by mutual entanglement to form a three-dimensional structure can reach as low as 0.035W / (m·K). Similar to conductive polymers, the Seebeck coefficient of carbon materials is not high. The third type is inorganic nano-semiconductor materials. The inorganic bulk thermoelectric materials that have been put into practical use have high conductivity and Seebeck coefficient, but have no flexible characteristics at all. Nano-sizing inorganic semiconductor materials can effectively improve their flexibility, and then using surfactants to disperse them in solvents, they can be used to prepare flexible thermoelectric films. However, surfactants tend to reduce the conductivity of inorganic semiconductors to a certain extent, so this method has certain limitations. In order to solve these problems, the main means of preparing flexible thermoelectric materials is to effectively regulate the thermoelectric properties of materials through chemical synthesis and molecular design strategies, morphology control and doping technology.
[0004] In addition, in order to obtain flexible thermoelectric devices with good flexibility, organic thermoelectric materials are usually used. Although organic polymers themselves have low thermal conductivity, their poor electrical conductivity leads to a low overall thermoelectric figure of merit (ZT = S 2*σ*T / κ As shown in the above formula, the ZT value is mainly characterized by three parameters, which require a high Seebeck coefficient (S) and electrical conductivity (σ), and low thermal conductivity (κ). These three parameters are related to the band structure of the material and are mutually restrained) and the conductivity type is basically p-type. There is currently no stable corresponding n-type thermoelectric material with good performance (the main carriers of n-type thermoelectric materials are electrons, and the direction of carrier movement is opposite to the direction of current), which seriously restricts the development and utilization of thermoelectric devices. In order to obtain n-type flexible thermoelectric materials with better performance, a large number of studies have focused on the synthesis of n-type inorganic thermoelectric material composites. For example, Bi 2 Te 3 However, due to its brittleness, the presence of rare and toxic Te elements, it is not conducive to practical wearable applications, and the introduction of insulating organic matter deteriorates the conductivity, thereby reducing the thermoelectric conversion efficiency. 2 As an "electronic crystal, phonon liquid" n-type thermoelectric material, Se has a ZT value (thermoelectric figure of merit) between 0.32 and 1.2 at room temperature, showing excellent thermoelectric performance. It is also environmentally friendly and has abundant reserves in the earth's crust. 2 Se becomes the ideal Bi 2 Te 3 Alternative materials.
[0005] Ag 2 Se flexible materials are prepared by a complex synthesis method, first by conventional melting and annealing to form a block material, and then sliced. This method has high energy consumption, and the power factor of the material is relatively low at room temperature. Another method often uses a conductive polymer with low thermal conductivity as the main material, or uses a flexible substrate with low thermal conductivity, such as filter membranes, polyimide (PI), polyethylene terephthalate, cellulose paper, etc. However, the carrier transport capacity of the polymer is very low, and the thermoelectric performance (including conductivity and power factor) of the thermoelectric film obtained by this method is very low, and it is difficult to meet the requirements of practical applications. How to maintain Ag 2 Se nanostructure, minimizing the use of insulators and obtaining flexible Ag with high flexibility and thermoelectric performance 2 Se thermoelectric thin films need further research.
[0006] Ti 3 C 2 T x As a unique n-type carbon-based material, it has a natural appeal. Due to its large interlayer spacing, good chemical stability, adjustable surface chemical properties, high conductivity and excellent flexibility, it has broad application prospects in the field of thermoelectrics. 3 C 2 T xIf used directly as a thermoelectric material, its thermal conductivity is high and does not meet the requirements.
[0007] At the same time, the prior art CN 115259157 B relates to a SnSe / Ti 3 C 2 Tx thermoelectric composite material and preparation method thereof, wherein Ti 3 C 2 T x The mass fraction y is 0.1-1wt%, and the preparation method comprises: adding a certain mass fraction of Ti 3 C 2 T x The dispersion was added to a round-bottom flask to prepare solution A. Then, a certain amount of NaOH and SnCl were added to solution A in sequence. 2 ·2H 2 O, stirred at room temperature until dissolved, then heated and stirred in an argon atmosphere until boiling to obtain solution B; at the same time, Se and NaBH 4 Add to deionized water in a certain proportion to prepare solution C; inject the prepared solution C into the boiling solution B, maintain the stirring rate and react at the boiling temperature; after the reaction stops and cools, collect the product by suction filtration, vacuum dry, and then obtain a dense block by discharge plasma spark sintering, i.e. SnSe / Ti 3 C 2 T x Thermoelectric composite materials. This invention uses a solution chemical synthesis method to achieve SnSe / Ti 3 C 2 T x The preparation of composite materials synergistically optimizes the thermoelectric and mechanical properties of SnSe. However, the reagent NaBH 4 When in contact with water, it releases highly flammable gas H 2 , it can cause combustion when in contact with water, moist air, acids, oxidants, high heat and open flames, and the agent is toxic by inhalation, skin contact and swallowing. And the technology uses discharge plasma spark sintering technology to obtain dense blocks, and the equipment used is expensive.
[0008] Prior art CN 111864045 A relates to a method for preparing a high-performance polyvinyl pyrrolidone / silver selenide / nylon flexible composite thermoelectric film, comprising the following steps: (1) using selenium nanowires as templates, reacting with silver nitrate in ethylene glycol solvent, adding polyvinyl pyrrolidone during the reaction to obtain a polyvinyl pyrrolidone-coated silver selenide multi-scale nanostructure; (2) dispersing the polyvinyl pyrrolidone-coated silver selenide multi-scale nanostructure in anhydrous ethanol, using a nylon filter membrane as a substrate, filtering, vacuum drying, and hot pressing to obtain the target product polyvinyl pyrrolidone / silver selenide / nylon composite film. Compared with the prior art, the invention can prepare a high-performance flexible thermoelectric film, and use the film to make a high-output performance thermoelectric device to power wearable electronic devices. However, the technology uses polyvinyl pyrrolidone, which is an organic polymer with poor electrical conductivity. In addition, polyvinyl pyrrolidone will be coated on the surface of silver selenide, which will reduce the conductivity of the prepared thermoelectric film, thereby affecting the performance of the manufactured thermoelectric device. Summary of the invention
[0009] The present invention aims to provide an n-type Ag with high conductivity. 2 Se / Ti 3 C 2 T x Thermoelectric composite material, preparation method thereof and application in preparing flexible film.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] A thermoelectric composite material, comprising Ag 2 Se and Ti 3 C 2 T x Compound obtained; Among them, Ti 3 C 2 T x The mass fraction is 0.2%-1.5%.
[0012] In one preferred embodiment, in the thermoelectric composite material, Ti 3 C 2 T x The mass fraction is 0.28%-1.12%.
[0013] High-performance thermoelectric materials need to achieve high power factor and low thermal conductivity by constructing heterojunctions, modulating heterostructures and chemical compositions, introducing interfaces, multi-level energy bands and defects, greatly regulating the carrier density and energy band structure of composite materials, and enhancing phonon scattering. 2 Se and Ti 3 C 2 T x Composite, prepared Ag2 Se / Ti 3 C 2 T x Composite structure, Ti 3 C 2 T x With Ag 2 The synergistic effect of Se structure introduces interfaces, multi-level energy bands and defects, enhances phonon scattering, and achieves high power factor and low thermal conductivity of thin film materials.
[0014] In one preferred embodiment, the Ag 2 Se has a rod-like structure.
[0015] In one preferred embodiment, the Ag 2 The length of Se is 1-8 μm and the cross-sectional diameter is 10-80 nm.
[0016] Ag in this length and size range 2 Se rod-like structure has good electrical conductivity.
[0017] In one preferred embodiment, the Ti 3 C 2 T x It is a three-dimensional network structure formed by flocculation of several layered structures.
[0018] The three-dimensional network structure formed by flocculation of several layered structures can be used as a framework to improve the flexibility and stability of the composite film. At the same time, compared with single-layer or multi-layer unflocculated two-dimensional layered structures, this construction method can introduce more interfaces, increase the sites of phonon scattering, and reduce the lattice thermal conductivity of the composite material.
[0019] In one preferred embodiment, the Ag 2 Se is Ti 3 C 2 T x pack.
[0020] Based on the same inventive concept, the present invention also claims a method for preparing the thermoelectric composite material, comprising the following steps:
[0021] S1. Preparation of Ti 3 C 2 T x :Ti 3 AlC 2Add to a mixed solution of concentrated hydrochloric acid and LiF, etch for 20-28 hours, take the etching solution and centrifuge and wash it several times until the solution is neutral, and collect the upper solution; continue to centrifuge and wash the etching solution and collect the upper solution until the upper solution is clear and stop collecting, and combine the collected upper solutions; add hydrochloric acid solution to the collected upper solution for flocculation, let it stand, centrifuge and wash, collect the precipitate, and obtain Ti 3 C 2 Tx;
[0022] S2. Preparation of Ag 2 Se / Ti 3 C 2 T x Composite materials: SeO 2 , β-cyclodextrin and Ti 3 C 2 After the mixture is evenly mixed, L-ascorbic acid solution is added dropwise, and the reaction is continued for 4-5 hours, and the precipitate is collected by centrifugation and washed. The washed product is dissolved in ethanol to obtain an ethanol solution; ammonium hydroxide is added to the ethanol solution, and the reaction is allowed to stand for 46-50 hours, and the product is collected and dissolved in ethanol to obtain Se / Ti 3 C 2 T x solution; AgNO was added successively 3 and L-ascorbic acid and stirred vigorously for 5-6 hours, and the product was collected to obtain the thermoelectric composite material (Ag 2 Se / Ti 3 C 2 T x composite materials).
[0023] In one preferred embodiment, the concentration of the hydrochloric acid solution in step S1 is 0.5-1.5M.
[0024] The concentration of the hydrochloric acid solution in step S1 will affect the flocculation speed. If the concentration is too low, the flocculation speed will be slow. If the concentration is too high, the flocculation will be too fast, resulting in too tight agglomeration.
[0025] In one preferred embodiment, the centrifugal washing in step S1 is performed by adding water to the etching solution and centrifuging at a speed of 8000-10000 r / min for 3-5 minutes.
[0026] In one preferred embodiment, Ti 3 AlC 2 The mass ratio of Ti to LiF is 0.1-0.5:1. 3 AlC 2 The molar ratio of 2-nitropropene to concentrated hydrochloric acid is 0.005-0.01:0.3-0.4.
[0027] The flocculent Ti 3 C2 Tx.
[0028] In one preferred embodiment, in step S2, SeO 2 and Ti 3 C 2 T x The mass ratio is 150-20:1.
[0029] SeO in step S2 2 and Ti 3 C 2 T x If the mass ratio of 2 If the Se content is too high, the Ti 3 C 2 T x A high content will affect the lattice thermal conductivity of the composite material.
[0030] In one preferred embodiment, in step S2, SeO 2 The mass ratio of β-cyclodextrin to 1-2:1-2.
[0031] SeO in step S2 2 The mass ratio of Se to β-cyclodextrin will affect the size of the Se rod-like structure. If it is too large, the rod diameter will be too large.
[0032] In one preferred embodiment, in step S2, SeO 2 The mass ratio of L-ascorbic acid added to the first addition is 1:3-6. If the amount of L-ascorbic acid added is too large, SeO 2 It cannot be completely restored, but if it is too small it will not have much impact.
[0033] In one preferred embodiment, in step S2, AgNO 3 and SeO 2 The molar ratio is 1.8-2.2:1.
[0034] Step S2: AgNO 3 and SeO 2 If the molar ratio is too large, there will be Ag impurities in the composite, and if the molar ratio is too small, there will be Se impurities in the composite.
[0035] In one preferred embodiment, the L-ascorbic acid and AgNO added for the second time in step S2 3 The molar ratio is 2-4:1.
[0036] The second addition of L-ascorbic acid and AgNO in step S2 3 If the molar ratio is too small, silver ions cannot be completely reduced to silver element, and if it is too large, there will be little effect.
[0037] Based on the same inventive concept, the present invention also claims to protect the application of the thermoelectric composite material in preparing a flexible film.
[0038] An n-type flexible film made of Ag 2 Se / Ti 3 C 2 T x The composite material is prepared.
[0039] The method for preparing the n-type flexible film comprises: 2 Se / Ti 3 C 2 T x The composite material is ultrasonically dispersed, vacuum deposited on a porous nylon membrane or a PVDF filter membrane, and then dried and hot-pressed to obtain the composite material.
[0040] In one preferred embodiment, the heat pressing is performed by manual heat pressing or mechanical heat pressing.
[0041] In one preferred embodiment, the manual hot pressing process is as follows: the temperature is 140-160° C. and the time is 3-10 min.
[0042] In one preferred embodiment, the mechanical hot pressing process is as follows: temperature is 140-180° C., time is 3-10 min, and pressure is 0.8-4 MPa.
[0043] The advantages of the present invention are:
[0044] (1) The preparation method of the present invention is simple, the raw materials are easy to obtain, the requirements for reaction equipment are low, the operation is simple, the conditions are mild, the preparation efficiency is high, the preparation process can be effectively simplified, and it is suitable for promotion and application; the Ag prepared by nylon filter membrane as the substrate 2 Se / Ti 3 C 2 T x The PF of the flexible thermoelectric film reached 1153.51 μW·m near room temperature. -1 ·K -2 , with excellent thermoelectric properties.
[0045] (2) The present invention adopts a method for constructing an n-type inorganic material with a heterojunction structure, and enhances the power factor of the material by adjusting the electronic structure and the energy band structure, thereby improving the thermoelectric performance of the material. This method provides a new idea for improving the performance of n-type thermoelectric materials. It expands the material system currently focused on the n-type inorganic field, and accelerates and enriches the application of n-type inorganic materials in the fields of thermoelectricity and electronics. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The flocculated Ti prepared in Example 13 C 2 T x , pure Ag 2 Se and Ag 2 Se / Ti 3 C 2 T x SEM images of composite materials; (a) flocculated Ti 3 C 2 T x , (b) is pure Ag 2 Se, (c) Ag 2 Se / Ti 3 C 2 T x Complex;
[0047] Figure 2 The flocculated Ti prepared in Example 1 3 C 2 T x 、Ag 2 Se / Ti 3 C 2 T x XRD patterns of composite materials;
[0048] Figure 3 To prepare the 3 C 2 T x Quality Ag 2 Se / Ti 3 C 2 T x Thermoelectric performance relationship diagram of flexible thermoelectric film; (a) and (b) are for adding 7.5 mg Ti 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x Thermoelectric performance of flexible thermoelectric films, (c) and (d) with 15 mg Ti added 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x Thermoelectric performance of flexible thermoelectric films, (e) and (f) with 30 mg Ti added 3 C 2 T x Ag 2 Se / Ti 3 C 2 T xThermoelectric properties of flexible thermoelectric films;
[0049] Figure 4 Ag 2 Se / Ti 3 C 2 T x Flexible thermoelectric film (added with 30mgTi 3 C 2 T x )'s conductivity versus temperature curve;
[0050] Figure 5 Ag with different heat pressing treatments 2 Se / Ti 3 C 2 T x Flexible thermoelectric film (added with 30mgTi 3 C 2 T x ) surface SEM image; where (a) the hot pressing conditions are 150°C, 5min, manual hot pressing, and (b) the hot pressing conditions are 180°C, 10min, 3Mpa. DETAILED DESCRIPTION
[0051] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0052] In the following examples, hydrochloric acid, ethylene glycol, AgNO 3 Selenium dioxide (SeO 2 ), β-cyclodextrin was purchased from Shanghai McLean Biochemical Technology Co., Ltd., L-ascorbic acid was purchased from Shanghai Titan Technology Co., Ltd., lithium fluoride was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and carbon titanium aluminum was purchased from Jilin Yiyi Technology Co., Ltd. The four-probe tester was from Guangzhou Four Probe Technology Co., Ltd., and the electrical performance test platform was independently designed and developed. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0053] Example 1
[0054] Preparation of flocculent Ti 3 C 2 T x 、Ag 2 Se and Ag 2Se / Ti 3 C 2 T x Thermoelectric Materials
[0055] (1) Flocculated Ti 3 C 2 T x Preparation: Pour 30 mL of concentrated hydrochloric acid into a polytetrafluoroethylene cup and place it in a 40°C water bath for heat preservation. Then slowly add 1.875 g of LiF into the concentrated hydrochloric acid and stir thoroughly for 10 minutes to dissolve. Finally, add 0.6 g of Ti 3 AlC 2 Add to a mixed solution of concentrated hydrochloric acid and LiF and etch for 24 hours. After etching, pour the solution into a centrifuge tube for sample washing and centrifuge with ultrapure water (centrifugal conditions are speed 9000r / min, time 3min). When the pH of the solution is 7, start collecting the upper layer solution after centrifugation, continue to centrifuge and wash repeatedly, and continue to collect the upper layer solution until the upper layer solution in the centrifuge tube becomes clear, then stop collecting and merge the collected upper layer solutions. In order to obtain Ti 3 C 2 T x Flocculation: add 1M hydrochloric acid to the collected solution for flocculation (according to the ratio of adding 10mL concentrated hydrochloric acid to 100mL solution), and let it stand overnight. After the flocculation is completed, pour out the supernatant of the solution, centrifuge and wash the flocculent precipitate (the centrifugation conditions are the same as those above), and finally obtain the target product.
[0056] (2) Ag 2 Se / Ti 3 C 2 T x Preparation of thermoelectric materials: 1g SeO 2 (molecular weight 110.96), 1g β-cyclodextrin and 30mg flocculent Ti 3 C 2 T x Add to a glass beaker containing 200 mL of distilled water and stir to form solution I. Add 5 g of L-ascorbic acid to 200 mL of distilled water and stir to form solution II. Slowly drip solution I into solution II and stir continuously. After reacting for 4 hours, collect the precipitate by centrifugation and wash it alternately with distilled water and anhydrous ethanol. Store the final product in 200 mL of anhydrous ethanol. Subsequently, add 20 μL of ammonium hydroxide to the above solution and let the solution stand at room temperature for 48 hours. Collect the obtained product by centrifugation and then disperse it in 200 mL of ethylene glycol. Add a certain amount of AgNO 3 and L-ascorbic acid were dissolved in 5 ml of distilled water. Then, AgNO 3 The solution was put into Se / Ti3 C 2 T x The molar ratio of Ag:Se precursors was 2:1. Then, L-ascorbic acid solution was added to the above dispersion, wherein L-ascorbic acid and AgNO 3 The molar ratio of Ag was 3:1. After vigorous stirring at room temperature for 5 h, the product was collected by centrifugation after the reaction was complete, and washed alternately with distilled water and ethanol, and finally dispersed in ultrapure water. 2 The molecular weight of Se is 294.7.
[0057] Pure Ag 2 Preparation of Se:
[0058] 1g SeO 2 , 1g β-cyclodextrin was added to a glass beaker containing 200mL of distilled water and stirred to form solution I. 5g L-ascorbic acid was added to 200mL of distilled water and stirred to form solution II. Solution I was slowly dripped into solution II with continuous stirring. After 4h of reaction, the precipitate was collected by centrifugation and washed alternately with distilled water and anhydrous ethanol. The final product was stored in 200mL of anhydrous ethanol. Subsequently, 20μL of ammonium hydroxide was added to the above solution, and the solution was allowed to stand at room temperature for 48h. The obtained product was collected by centrifugation and then redispersed in 200mL of ethylene glycol. A certain amount of AgNO 3 and L-ascorbic acid were dissolved in 5 ml of distilled water. Then, AgNO 3 The solution was put into Se / Ti 3 C 2 T x The solution was stirred vigorously. The molar ratio of Ag:Se precursor was 2:1. Subsequently, L-ascorbic acid solution was added to the above dispersion, wherein L-ascorbic acid and AgNO 3 The molar ratio is 3: 1. After vigorous stirring at room temperature for 5 hours, the product was collected by centrifugation after the reaction was complete, washed alternately with distilled water and ethanol, and finally dispersed in ultrapure water.
[0059] The obtained flocculated Ti 3 C 2 T x , pure Ag 2 Se, Ag 2 Se / Ti 3 C 2 T x Composite materials are tested by SEM, such as Figure 1 As shown in a, it can be seen that the flocculated Ti obtained by etching 3 C 2 T xThe morphology is large-scale layered and the distribution is relatively uniform. This structure can serve as a good support structure for the film. Figure 1 b is pure Ag 2 SEM image of Se, its morphology is a nanorod-like structure. Figure 1 c is the addition of Ag 2 Se / Ti 3 C 2 T x SEM image of the composite. By comparison, it can be clearly noticed that the nanorod materials with higher brightness are connected and wrapped by the materials with lower brightness, and it can be clearly observed that the nanorod-like structure materials are wrapped by the layered materials. 2 Se has a length of 8 μm and a cross-sectional diameter of 40 nm. 2 Se / Ti 3 C 2 T x The complex was successfully synthesized.
[0060] The obtained flocculated Ti 3 C 2 T x , Ag 2 Se / Ti 3 C 2 T x The composite material is XRD patterned, with 2theta being the diffraction angle. Figure 2 It can be seen that Ti 3 AlC 2 Flocculated Ti obtained after selective etching of powder 3 C 2 T x In the XRD spectrum of Ti, no diffraction peak (104) at around 39° is observed, which indicates that 3 AlC 2 The Al layer has been successfully eliminated, and compared with Ti 3 AlC 2 The diffraction peak of the powder at 9.6° shows that the diffraction peak of (002) phase has an obvious left shift, indicating that Ti 3 C 2 T x The interlayer distance of the flocculated Ti is significantly increased. 3 C 2 T x Has been successfully obtained. 2 Se / Ti 3 C 2 T x The XRD patterns of the composite samples are consistent with those of PDF card #24-1041 (Ag 2Se standard XRD spectrum) is relatively consistent, indicating that Ag 2 Se / Ti 3 C 2 T x Synthesized Ag in the composite 2 Se has good crystallinity. In addition, the synthesized Ag 2 Se nanorods exhibit orthorhombic β-Ag 2 Se, space group P212121. And represents Ti 3 C 2 T x The diffraction peak of was not clearly observed, which may be because the content in the composite sample is relatively small and the diffraction peak is relatively small.
[0061] Example 2
[0062] The composite materials prepared in Example 1 and the comparative example were used to prepare thermoelectric thin films. The preparation process was as follows: a certain amount of the composite materials were dispersed in an aqueous solution by ultrasonic bath in an ice bath for 30 minutes using an ultrasonic cell crusher. Subsequently, the composite materials were deposited on a porous nylon membrane or a PVDF filter membrane by vacuum assisted filtration. The prepared film was dried at 60°C under vacuum overnight. In addition, Ag 2 Se-based flexible thermoelectric films were subjected to different hot pressing treatments. When a manual hot press (which can only control the temperature) was used to press the films, the hot pressing temperature was kept at 150°C and the time was 5 minutes.
[0063] Comparative Example 1: Polyvinyl pyrrolidone / silver selenide / nylon flexible composite thermoelectric film, prepared with reference to Example 1 of the prior art CN111864045A.
[0064] Comparative Example 2: Ag 2 Se / polyvinyl pyrrolidone (PVP) composite film, referring to the prior art Zhao Y, Liu D, Yan Z, Zhang Z, Zheng Y, Zhang Y, Xue C. Preparation and characterization of the Ag 2 Preparation of Se flexible films tuned by PVP for wearable thermoelectric generator[J]. Journal of Materials Science: Materials in Electronics, 2021, 32, 20295-20305. DOI: 10.1007 / s10854-021-06535-9.
[0065] Comparative Example 3: Polyvinylidene fluoride (PVDF) / Ag2 Se thermoelectric film, referring to the prior art Zhou H, Zhang Z, Sun C, Deng H, Fu Q.Biomimetic approach to facilitate the high filler content in free-standing and flexible thermoelectric polymer composite films based on PVDF and Ag 2 Preparation of Se nanowires[J].ACS Applied Materials&Interfaces,2020,12(46),51506-51516.DOI:10.1021 / acsami.0c15414.
[0066] Comparative Example 4: Flocculated Ti 3 C 2 T x The preparation method does not add 1M hydrochloric acid for flocculation at the end, and directly takes the upper layer solution (containing the layered structure of Ti 3 C 2 T x ) to conduct subsequent thermoelectric material preparation experiments.
[0067] The performance of the films prepared in the above examples and comparative examples was tested as follows:
[0068] (1) Calculation of the Seebeck coefficient of the film: According to the definition of the Seebeck effect, the Seebeck coefficient can be calculated from the ratio of the voltage difference between the two ends of the material and the temperature difference ΔT between the cold end and the hot end (S = ΔV / ΔT). Through the self-built flexible thermoelectric thin film power generation device performance test platform, the cut thermoelectric film is placed on two copper thermal conductive modules, and then the thermoelectric film or device is connected to a thermocouple and a copper wire. These thermocouples and wires are connected to the Keithley semiconductor parameter meter DAQ6510 / 7700. When the copper thermal conductive module at one end is heated, the temperature of one end of the thermoelectric film or device will rise. When a temperature difference is generated, the voltage difference and temperature change data at both ends of the thermoelectric film or device can be recorded through the program designed by the software KickStart on the semiconductor parameter meter to calculate the Seebeck coefficient of the thermoelectric material at room temperature.
[0069] (2) Film resistivity test: The present invention uses an RTS-9 dual-electric four-probe tester to test the resistivity of the flexible film. The resistivity tester can measure the range of 10 -5 ~10 5Ωcm, probe spacing is: 1±0.01mm, and the thickness of the tested sample must be less than or equal to 3mm. By installing the heating resistor on the test stage and connecting the thermoelectric pair, the resistivity of the thermoelectric film can be tested as it changes with temperature. The conductivity value can be calculated from the resistivity (σ=1 / ρ).
[0070] The results show that Figure 3 e and 3f, 30 mg Ti was added 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x The PF of the flexible thermoelectric film made with nylon filter membrane as the substrate is the largest, reaching 106μW·m near room temperature. -1 ·K -2 , which is due to its optimal conductivity.
[0071] After hot pressing at 150° C. for 5 minutes, the conductivity of the material of Comparative Example 1 is much lower than that of the composite material prepared in Example 1. The hot pressing temperature makes it difficult for the silver selenide grains to grow sufficiently, and thus the thermoelectric performance of the film cannot be greatly improved.
[0072] Comparative Example 2 Ag 2 After hot pressing at 150℃ for 5 min, the maximum PF value of Se / PVP composite film was only 16.18 μW·m -1 ·K -2 .
[0073] Comparative Example 3 Polyvinylidene fluoride (PVDF) / Ag 2 The maximum PF value of Se thermoelectric film after hot pressing at 150℃ for 5 min is 59.10μW·m -1 ·K -2 .
[0074] It can be seen that although the addition of PVDF and PVP can reduce thermal conductivity, due to their insulation properties, it also reduces the electrical conductivity and thermoelectric properties of the film.
[0075] Comparative Example 4 containing a two-dimensional layered structure of Ti 3 C 2 T x After hot pressing at 150℃ for 5 min, the maximum PF value of the prepared composite film was only 0.7 μW·m -1 ·K -2 .
[0076] Example 3
[0077] Based on Example 1, adjust the flocculent Ti3 C 2 T x The masses of the products were 7.5 mg, 15 mg, and 30 mg, respectively, and the others were consistent with those in Example 1. 3 C 2 T x Quality Ag 2 Se / Ti 3 C 2 T x The composite material was used to prepare the thermoelectric film. The preparation process was the same as in Example 2 to obtain the composite material containing different Ti 3 C 2 T x Quality Ag 2 Se / Ti 3 C 2 T x Flexible thermoelectric film. The thermoelectric performance of the film is analyzed and the data obtained are as follows Figure 3 shown.
[0078] Figure 3 (a) and (b) show the addition of 7.5 mg Ti 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x Thermoelectric performance of flexible thermoelectric films, (c) and (d) with 15 mg Ti added 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x Thermoelectric performance of flexible thermoelectric films, (e) and (f) with 30 mg Ti added 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x Thermoelectric properties of flexible thermoelectric films. Figure 3 (a) Figure 3 (c) Figure 3The red curve in (e) represents the curve of the conductivity of the three materials made of nylon filter membrane as the substrate and the curve of the conductivity of the three materials made of PVDF filter membrane as the substrate. It can be seen from these three figures that the conductivity of the six films increases with the increase of temperature, indicating that the six films all show semiconductor properties. It can be clearly seen from these three comparison figures that the addition of 30mg Ti 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x The electrical conductivity of the flexible thermoelectric film is significantly improved due to the addition of a large amount of Ti 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x Make Ag 2 The Se nanorods were initially loosely connected with high potential barriers resulting in severe electron transport scattering, but now are in close contact with significantly reduced electron scattering. Figure 3 (b) Figure 3 (d) Figure 3 In (f), the circle represents the use of nylon filter membrane as the substrate, and the triangle represents the use of PVDF filter membrane as the substrate. The linearity represents the relationship between the voltage difference at both ends of the six films and the change in temperature. According to the definition of the Seebeck coefficient, its value can be calculated from the ratio of the voltage difference to the temperature difference. 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x The Seebeck coefficients of the flexible thermoelectric films were -90.43 μV / K and -82.95 μV / K, respectively. 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x The Seebeck coefficients of the flexible thermoelectric films were -83.27 μV / K and -86.12 μV / K, respectively. 3 C 2 T xAg 2 Se / Ti 3 C 2 T x The Seebeck coefficients of the flexible thermoelectric films are -84.50μV / K and -87.98μV / K respectively. The Seebeck coefficients of the six flexible thermoelectric films are all negative, indicating that the prepared Ag 2 Se / Ti 3 C 2 T x The flexible thermoelectric film is an n-type semiconductor, and regardless of the addition of Ti 3 C 2 T x , using nylon / PVDF filter membrane as substrate, or hot pressing treatment have no effect on the intrinsic conductivity type of thermoelectric materials. In addition, the Seebeck coefficient is slightly different, which is mainly because the Seebeck coefficient is an intrinsic parameter of thermoelectric materials. When the composition of flexible thermoelectric film is constant, its Seebeck coefficient is basically determined. According to the dimensionless thermoelectric figure of merit (S 2 σT / κ) shows that when the film thickness is small and thermal conductivity is not considered, the thermoelectric performance of the flexible thermoelectric film mainly depends on the power factor (which is S 2 σ), calculated by adding 30 mg Ti 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x The PF of the flexible thermoelectric film made with nylon filter membrane as the substrate is the largest, reaching 106μW·m near room temperature. -1 ·K -2 , which is due to its optimal conductivity. In short, adding Ti 3 C 2 T x Can significantly increase Ag 2 The thermoelectric performance of Se flexible thermoelectric film was investigated, and the flexible thermoelectric film using nylon filter membrane as substrate showed the best thermoelectric performance.
[0079] Example 4
[0080] On the basis of Example 1, the concentrations of the hydrochloric acid solution used for flocculation were adjusted to 0.5 M, 1.25 M, and 1.5 M, respectively, and the other concentrations were kept the same as in Example 1 to obtain different Ag 2 Se / Ti 3 C 2 T x The composite material was used to prepare the thermoelectric film. The preparation process was the same as in Example 2 to obtain different Ag2 Se / Ti 3 C 2 T x Flexible thermoelectric film. The thermoelectric performance of the film was analyzed and the results showed that different Ag 2 Se / Ti 3 C 2 T x After the flexible thermoelectric film was hot-pressed at 150°C for 5 minutes, its power factor was between 90-110 μW·m -1 ·K -2 between.
[0081] Example 5
[0082] Based on Example 1, adjust SeO 2 and Ti 3 C 2 T x The mass ratios of Ag and Mg were 150:1, 100:1, and 50:1, respectively, and the others were consistent with Example 1 to obtain different Ag 2 Se / Ti 3 C 2 T x The composite material was used to prepare the thermoelectric film. The preparation process was the same as in Example 2 to obtain different Ag 2 Se / Ti 3 C 2 T x Flexible thermoelectric film. The thermoelectric performance of the film was analyzed and the results showed that different Ag 2 Se / Ti 3 C 2 T x After hot pressing at 150℃ for 5 minutes, the power factor of the flexible thermoelectric film is between 85-101μW·m -1 ·K -2 between.
[0083] Example 6
[0084] The composite material prepared in Example 1 was used to prepare thermoelectric thin films. The preparation process was the same as in Example 2, except that the hot pressing was replaced by a hot press. The hot pressing temperature was 150°C and 180°C, the pressure was 1, 2, and 3 MPa, and the time was 5 min and 10 min.
[0085] The heat pressing function of the multifunctional thermal conductivity tester DRL-V was used to test the nylon filter membrane as the substrate and 30 mg Ti was added 3 C 2 T x Ag 2 Se / Ti 3 C 2 Tx The produced flexible film was subjected to heat pressing and the conductivity of the film under different heat pressing conditions was tested as it changes with temperature. The results are as follows: Figure 4 The diamond in the figure represents the conductivity change trend of the film with temperature after manual hot pressing at 150°C for 5 minutes using the WT-90GS small manual hot stamping machine. The data here are used for comparison. Other hot pressing conditions were completed using the hot pressing function of the multi-function thermal conductivity tester DRL-V. Figure 4 The conductivity-temperature change relationship diagram of the film under different hot pressing conditions ((150℃, 1Mpa, 5min), (150℃, 2Mpa, 5min), (180℃, 3Mpa, 10min)) is given. It can be clearly seen from the figure that with the increase of hot pressing pressure and temperature, the conductivity of the film is significantly improved. When the hot pressing condition is 180℃, 3Mpa, 10min, the conductivity of the film is the largest. Unfortunately, due to the limitations of the hot pressing instrument function and the heat resistance temperature of the nylon film, the pressure and temperature in the hot pressing cannot be further increased. Therefore, the hot pressing conditions in the present invention can only be determined to be 180℃, 3Mpa, 10min. Under this hot pressing condition, 30mgTi was added 3 C 2 T x Ag 2 Se / Ti 3 C 2 T x The conductivity of the flexible thermoelectric film made with nylon filter membrane as the substrate is 902.24S / cm near room temperature, and its Seebeck coefficient is -113.07μV / K after testing. Finally, the PF of the thermoelectric film reaches 1153.51μW·m -1 ·K -2 The reason may be that the increase of hot pressing pressure and temperature during hot pressing makes the film denser.
[0086] Ag with different hot pressing treatments 2 Se / Ti 3 C 2 T x (Add 30mg Ti 3 C 2 T x ) SEM image of the flexible thermoelectric film surface Figure 5 As shown, (a) the hot pressing conditions are 150°C, 5 min, manual hot pressing, and (b) the hot pressing conditions are 180°C, 10 min, 3Mpa. Figure 5 It can be clearly seen that under manual hot pressing, under a small pressure, there are a lot of loose structures on the film surface, among which Ag 2 Se / Ti 3 C 2T x The gaps between the composites are wide, and the distribution is loose with a lot of voids. However, the surface of the film treated with strong hot pressing temperature and pressure is relatively dense. 2 The Se nanorods overlap closely with each other. Figure 5 (b) Ag in the middle area 2 Se / Ti 3 C 2 T x It is difficult to distinguish them, which is due to the bonding effect of MXene. In short, hot pressing can make Ag 2 Se / Ti 3 C 2 T x The surface of the thermoelectric film is dense, and the thermoelectric particles form better ohmic contact with each other.
[0087] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A thermoelectric composite material, characterized in that: Composed of Ag2Se and Ti3C2T x Composite obtained; Among them, Ti3C2T x The mass fraction is 0.2%-1.5%.
2. The thermoelectric composite material according to claim 1, characterized in that: The Ag2Se is a rod-shaped structure; the length of the Ag2Se is 1-8µm, and the cross-sectional diameter is 10-80 nm.
3. The thermoelectric composite material according to claim 1, characterized in that: The Ti3C2T x It is a three-dimensional network structure formed by flocculation of several layered structures.
4. The thermoelectric composite material according to any one of claims 1 to 3, characterized in that: The Ag2Se is replaced by the Ti3C2T x pack.
5. The method for preparing the thermoelectric composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Preparation of Ti3C2T x : Add Ti3AlC2 to a mixed solution of concentrated hydrochloric acid and LiF, etch for 20-28 h, take the etching solution and wash it by centrifugation several times until the solution is neutral, and collect the upper solution; Continue to centrifuge and wash the etching solution and collect the upper solution until the upper solution becomes clear and stops collecting, and combines the collected upper solutions; Add hydrochloric acid solution to the collected upper solution for flocculation, let stand, centrifuge and wash, collect the precipitate, and obtain Ti3C2T x ; S2. Preparation of Ag2Se / Ti3C2T x Composite materials: SeO2, β -Cyclodextrin and Ti3C2T x Mix well and add L - Ascorbic acid solution, after reacting for 4-5 hours, centrifuge to collect the precipitate, wash, and dissolve the washed product in ethanol to obtain an ethanol solution; Add ammonium hydroxide to the ethanol solution, let it react for 46-50 hours, collect the product and dissolve it in ethanol to obtain Se / Ti3C2T x solution; in which AgNO3 and L -ascorbic acid and vigorously stirring for 5-6 hours, collecting the product to obtain the thermoelectric composite material.
6. The preparation method according to claim 5, characterized in that: The concentration of the hydrochloric acid solution in step S1 is 0.5-1.5M.
7. The preparation method according to claim 5, characterized in that: The mass ratio of Ti3AlC2 to LiF is 0.1-0.5:1, and the molar ratio of Ti3AlC2 to concentrated hydrochloric acid is 0.005-0.01:0.3-0.
4.
8. The preparation method according to claim 5, characterized in that: SeO2 and Ti3C2T in step S2 x The mass ratio of SeO2 and β -The mass ratio of cyclodextrin is 1-2:1-2; the molar ratio of AgNO3 and SeO2 in step S2 is 1.8-2.2:
1.
9. An n-type flexible film, characterized in that: The thermoelectric composite material is prepared from any one of claims 1 to 4.
10. The n-type flexible film according to claim 9, characterized in that: The method for preparing the n-type flexible film comprises: x After ultrasonic dispersion, the composite material is vacuum deposited on a porous nylon membrane or a PVDF filter membrane, dried, and hot pressed; preferably, the hot pressing is performed by manual hot pressing or mechanical hot pressing, wherein the manual hot pressing process is as follows: the temperature is 140-160°C, the time is 3-10min; the mechanical hot pressing process is as follows: the temperature is 140-180°C, the time is 3-10min, and the pressure is 0.8-4 Mpa.
Citation Information
Patent Citations
Method for preparing high-performance polyvinylpyrrolidone / silver selenide / nylon flexible composite thermoelectric film
CN111864045A
A SnSe / Ti3C2T x Thermoelectric composite materials and their preparation methods
CN115259157B